2010
DOI: 10.1007/s10865-010-9281-9
|View full text |Cite
|
Sign up to set email alerts
|

Brief integrative multiple behavior intervention effects and mediators for adolescents

Abstract: This study evaluated the efficacy of a brief integrative multiple behavior intervention and assessed risk factors as mediators of behavioral outcomes among older adolescents. A randomized controlled trial was conducted with participants randomly assigned to either a brief intervention or standard care control with 3-month follow-up. A total of 479 students attending two public high schools participated. Participants receiving the intervention showed a significant reduction in quantity x frequency of alcohol us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In a public health intervention aimed at enhancing multiple health behaviors in high school adolescents,150 positive outcomes included reductions in alcohol use and increases in fruit and vegetable consumption and participation in relaxation activities. Sleep measures, exercise, cigarette and marijuana use remained unchanged.…”
Section: Treatment Of Lifestyle and Technology Related Sleep Disturbamentioning
confidence: 99%
“…In a public health intervention aimed at enhancing multiple health behaviors in high school adolescents,150 positive outcomes included reductions in alcohol use and increases in fruit and vegetable consumption and participation in relaxation activities. Sleep measures, exercise, cigarette and marijuana use remained unchanged.…”
Section: Treatment Of Lifestyle and Technology Related Sleep Disturbamentioning
confidence: 99%
“…A randomized trial of a brief intervention targeted at multiple behaviors delivered in 2 public high schools found a significant decrease in alcohol use [90]. An evaluation of an early intervention found it feasible for school nurses to assess and conduct brief interventions for substance-using adolescents [91].…”
Section: Sbirt and Adolescentsmentioning
confidence: 99%
“…The concept of hedonic substitution, replacement of one rewarding behavior with another, is a promising area of research. Exercise has been used in the past to help reduce ethanol intake in heavy drinkers (Correia et al, 2005; Murphy et al, 1986; Weinstock, 2010; Werch et al, 2011), and animal studies have shown consistent interaction effects with ethanol consumption (Darlington et al, 2014; Ehringer et al, 2009; Hammer et al, 2010; McMillan, 1978; McMillan et al, 1995; Ozburn et al, 2008; Werme et al, 2002). However, little is known about the neurobiology of this interaction.…”
Section: Introductionmentioning
confidence: 99%